In vitro analysis of n-acetylcysteine (NAC) interference with the international normalized ratio (INR) - Minhaj, Faisal Syed; Leonard, James B.; Seung, Hyunuk; Anderson, Bruce D.; Klein-Schwartz, Wendy; King, Joshua D. (Clinical toxicology (Philadelphia, Pa.), 2022)
Previous literature suggests a laboratory interference of n-acetylcysteine (NAC) with prothrombin time (PT) and the international normalized ratio (INR). Early publications focused on this interaction in the setting of an acetaminophen overdose and evaluated the INR of patients receiving intravenous NAC. However, there is limited literature describing the concentration-effect relationship of NAC to INR measurement in the absence of acetaminophen-induced hepatotoxicity at therapeutic NAC concentrations. The purpose of the study is to quantify the degree of interference of NAC on INR values at therapeutic concentrations correlating to each infusion of the regimen (ex. bag 1: 550 mcg/mL, bag 2: 200 mcg/mL, bag 3: 35 mcg/mL, double bag 3: 70 mcg/mL) and at supratherapeutic concentrations in vitro. Blood samples were obtained from study volunteers. Each blood sample was transferred into vials containing 0.3 mL buffered sodium citrate 3.2% and spiked with various concentrations of NAC for final concentrations of 0, 35, 70, 200, 550, 1000, 2000, and 4000 mcg/mL. The samples were centrifuged and tested to determine PT and INR on two separate machines: Siemens CS-2500 and Stago SN1114559. We would require a sample size of 6 to achieve a power of 80% and a level of significance of 1.7% (two-sided). Differences between INRs at varying concentrations were determined by Friedman's test. For multiple comparisons, post hoc analysis was performed using Wilcoxon signed-rank test with Bonferroni adjustment. Analyses were performed with SAS version 9.4 (SAS Institute, Cary, NC). Participants included 11 healthy subjects: 8 males, 3 females, median age 30 years (range 25 − 58). Median and interquartile ranges (IQR) INR for the baseline samples were 1.09 (IQR 1.05, 1.16) for Siemens and 1.03 (IQR 0.99, 1.11) for Stago analyzers. There was a significant difference in INR between the therapeutic concentrations (baseline, 35, 70,200, or 550 µg/mL) (Siemens p = .0008, Stago p < .0001). The 550 µg/mL concentration with the Siemens analyzer was the only one compared separately and found to be significantly greater than the baseline (1.07 vs 1.22, p = .02). For the Stago analyzer the 200 µg/mL and 500 µg/mL were compared and found to be significantly different from baseline (1.00 vs 1.07 and 1.19, adjusted p = .02 and p = .03, respectively). The largest INR increase seen was in one subject from a baseline of 1.07-1.32 with the 550 µg/mL concentration. Increases in concentrations to supratherapeutic levels resulted in a statistically significant non-linear increase in INR for all concentrations (Siemens p < .0001, Stago p < .0001). All of these concentrations were found to be significantly different from baseline (all adjusted p < .05). Although it was found that at therapeutic concentrations the in vitro presence of NAC affects INR measurements on two different machines, the change is of little clinical relevance. Supratherapeutic concentrations of NAC affect INR significantly, but the clinical utility of those results is limited by the rarity of those concentrations being measured.